Two new species of Cypella (Iridaceae: Tigridieae) from Rio Grande do Sul, Brazil - Deble, Leonardo Paz; de Oliveira Deble, Anabela Silveira; Alves, Fabiano Da Silva (Phytotaxa, 2012)
Cypella luteogibbosa and C. magnicristata are described, illustrated and have their taxonomic affinities discussed. The former is related with C. fucata, but differs by white flowers (vs. pallide orange) and divergent adaxial crests of style apices (vs. convergent). From Cypella osteniana the new species differs by 1-flowered spathes (vs. 2-flowered), spatulate outer tepals, 10–12 mm wide (vs. obovate, 15–17 mm wide), inner tepals with a yellow hump abaxially, and keel-shaped distally (vs. without a hump, and folded distally), and anthers with narrowed connective (0.6–0.9 mm vs. 1.4–1.8 mm). Cypella magnicristata is related with C. armosa, but differs mostly by obovate outer tepals, 38–44 × 22–25 mm (vs. spatulate, 36–40 × 12–16 mm), larger inner tepals (22–24 × 15–16 mm vs. 14–18 × 10–12 mm), and longer filiform filaments (5.5–6.4 mm vs. 3–3.5 mm). From C. exilis the new species differs mostly by diameter of flowers (60–70 mm vs. 38–48 mm), bigger size of outer tepals (38–44 × 22–25 vs. 32–36 × 12–16 mm), larger inner tepals (22–24 × 15–16 vs. 12–15 × 8–9 mm), and length of crests of style apices (6–7 mm vs. 4–5 mm).